EMPLOYED PATTERN LOW-EDUCATED AND HIGH-EDUCATED WORKERS IN INDONESIA: A BINARY LOGISTIC REGRESSION APPROACH - Nur Mardiansyah; Suharno Suharno; Muhammad Farid Alfarisy (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2022)
This research is motivated by an increase in investment, gross domestic product, government expenditure, and wages but does not cause an increase in employment. This study aimed to analyze the effect of independent variables on employment-based low and high education. The novelty of this research is to use the binary logistic regression method. The data used is secondary data province in Indonesia. The analysis results show that gross domestic product and wages have more influence on the employment of highly educated workers. Domestic investment has a significant negative effect on employment. So that domestic investment has more influence on the employment of low-educated workers. The recommendation from this research is that the government must pay attention to workforce education to keep up with the times. The limitation of this study is that there are empty data in the province of North Kalimantan.